PENGARUH LEADER MEMBER EXCHANGE DAN MASA KERJA PADA WORK ENGAGEMENT PEGAWAI DINAS XYZ - Cisilia Prilestari (Jurnal Manajemen Kepegawaian, 2019)
Bureaucratic reform is the first milestone in efforts to improve the performance of public services in Indonesia. Organizational performance is the responsibility of every part of the organization, including the human resources. For this reason, it is necessary to manage the right human resources to achieve organizational goals, one of which is to improve employee’s engagement work. This study aims to determine the relationship between leader-member exchange (LMX) and work engagement and measure the effect of tenure as a moderator on the relationship between the two variables. The sample used in this study is Civil Servants (PNS) at Dinas XYZ. The data collected were 194 participants, which processed using the Hayes’process moderation analysis technique in SPSS. Furthermore, the measuring instrument used to measure work engagement was 10 items of UWES (Utrecht Work Engagement Scale) and 12 item of the LMX-MDM Questionnaire. Based on the results of data analysis, it was found that LMX is positively related and predicts work engagement significantly, but the role of tenure as a moderator is not proven.